Effect of magnesium and fluorine dopants on properties of ZnO thin films - Sutatip Thonglem (2018)
© 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved. Effects of Mg and F codoping on properties of ZnO films were studied in this work. F and Mg codoped ZnO films with a fixed Mg concentration of 20 at% and 0-8 at% F concentration were deposited on microscope glass substrates by the ultrasonic spray pyrolysis. The morphology of all films showed a spherical grain shape, and F doping decreased roughness with the addition of F concentration as well as decreased grain size with doping higher than 4 at% of films. The XRD patterns of all films were identified as a polycrystalline hexagonal wurtzite structure of ZnO with (002) preferred orientation. The band gap of 0 at% F doping film was 3.69 eV, which decreased to a minimum with 2 at% F doping and increased again with higher than 2 at% F doping. F doping decreased resistivity to a minimum with addition until 4 at% F doping and then increased again with higher than 4 at% F doping.